1996
DOI: 10.1002/(sici)1099-1034(199606)31:2<143::aid-gj704>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Glacial activity and paraglacial landsliding in the Devensian Lateglacial: evidence from Craig Cerrig-gleisiad and Fan Dringarth, Fforest Fawr (Brecon Beacons), South Wales

Abstract: The tongue-shaped mass of debris and associated ridges on the cirque floor below Craig Cerrig-gleisiad. BreconBeacons National Park is important and controversial because it has been attributed to more than one glacier advance during the Late Devensian. A new origin is proposed involving landslide development from the collapse of part of the western headwall followed by a single phase of glacier development in the Loch Lomond Stadial (Younger Dryas), which reworked the landslide sediments. Evidence for this la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
(9 reference statements)
1
40
0
Order By: Relevance
“…In the mountains of Great Britain, a small number of rock-slope failures are known to have occurred during the Late Devensian Lateglacial, during the interval between ice-sheet deglaciation and the beginning of the Holocene (e.g. Ballantyne, 1986b;Shakesby and Matthews, 1996), but surface exposure dating using cosmogenic isotopes has shown that other major landslides occurred much later. A major rockslide at The Storr on the Isle of Skye occurred at 6.5 AE 0.5 ka (Ballantyne et al, 1998), a massive rock avalanche on Beinn Alligin in the NW Highlands has been dated to 4.0 AE 0.3 ka (Ballantyne and Stone, 2004) and a rock avalanche near Glencoe has been dated to ca.…”
Section: Paraglacial Landscape Modificationmentioning
confidence: 99%
“…In the mountains of Great Britain, a small number of rock-slope failures are known to have occurred during the Late Devensian Lateglacial, during the interval between ice-sheet deglaciation and the beginning of the Holocene (e.g. Ballantyne, 1986b;Shakesby and Matthews, 1996), but surface exposure dating using cosmogenic isotopes has shown that other major landslides occurred much later. A major rockslide at The Storr on the Isle of Skye occurred at 6.5 AE 0.5 ka (Ballantyne et al, 1998), a massive rock avalanche on Beinn Alligin in the NW Highlands has been dated to 4.0 AE 0.3 ka (Ballantyne and Stone, 2004) and a rock avalanche near Glencoe has been dated to ca.…”
Section: Paraglacial Landscape Modificationmentioning
confidence: 99%
“…It therefore is unlikely that ridges A and B are of protalus origin, although Shakesby (1997) has suggested that the rampart-talus distances reported by Ballantyne and Kirkbride (1986) may not be diagnostic of rampart origins. The arcuate plan of ridges A and B is unlikely to have originated from landsliding because there is no evidence of backward-tilting blocks or of tension cracks adjacent to the backwall, nor of lateral ridges and an upstanding terminus on the bench at 2000 m, all of which are diagnostic of landslides (Shakesby and Matthews, 1996). Shakesby (1992) considers that rock avalanches result in 'splays of debris forming ridges and mounds of debris'.…”
Section: Ridge Originmentioning
confidence: 99%
“…Some of the clasts within the deposits that form ridges A and B, where A is superimposed on B (Fig. 3), are striated, which strongly indicates a glacial origin (Boulton, 1978;Shakesby and Matthews, 1996). The particle size composition of the fine matrix of the sediments at the same site (Table 1) the particle-size distribution envelopes characteristic of lodgement and of melt-out tills (Sladen and Wrigley, 1983), although these envelopes are broad and therefore may not be diagnostic.…”
Section: Ridge Originmentioning
confidence: 99%
“…Similarly, even when moraines have been inferred to pre-date the LLS, usually based on their more subdued appearance and greater size, the lack of absolute dates on these landforms means a LLS age cannot be ruled out. The glacial origin of some features has also been questioned, especially where moraines may appear similar in morphology to protalus ramparts or landslide blocks (Shakesby & Matthews, 1996). In cases of both uncertain age and genesis, this project assumes a LLS origin, especially if location appears consistent with the maximum extent of LLS glaciation, unless subsequent literature strongly refuted such an interpretation.…”
Section: Limitationsmentioning
confidence: 99%